Pengaruh Motivasi Kerja, Stres Kerja, Dan Kompensasi Terhadap Produktivitas Kerja Karyawan Bank Mandiri Kantor Cabang Pembantu Di Surabaya - Leonita Yani Larasati (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2026)
This study aims to analyze the effect of work motivation, job stress, and compensation on employee work productivity at Bank Mandiri Se-Surabaya Branch. The research adopts a quantitative approach with a causal associative research design. The population of this study consists of all employees at Bank Mandiri Se-Surabaya Branch. A saturated sampling technique was applied, in which all members of the population were included as research respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that work motivation has a positive and significant effect on employee work productivity. Job stress has a negative and significant effect on employee productivity, implying that higher levels of job stress tend to reduce employee productivity. Meanwhile, compensation has a positive and significant effect on work productivity, suggesting that fair and performance-based compensation can enhance employee productivity. Simultaneously, work motivation, job stress, and compensation significantly influence employee work productivity. The coefficient of determination shows that the independent variables explain a substantial proportion of the variation in employee productivity. The findings highlight the importance of managing work motivation, controlling job stress, and implementing a fair compensation system to improve employee productivity in the banking sector.